‘Its native surroundings’: Marianne Moore, England, and the idea of the ‘characteristic American’ - Stubbs, T (Edinburgh University Press, 2016)
Marianne Moore claimed that she was ‘Irish by descent, possibly Scotch also, but purely Celtic’. Critics have gone so far as to claim Moore as an Irish-American poet. In so doing they have glossed over the English side of her family background (as did Moore herself). This is perhaps unsurprising, considering that it was Moore's father, from whom she was estranged throughout her life, who was of English ancestry. Nevertheless, this ancestry lurks in the background of her imagination. This article argues that Moore's poetry and prose often map ‘Englishness’ onto ‘Americanness’. Here she is both the American tourist and the American settler, engaging with a colonial legacy upon which Englishness has been heavily imprinted. By considering the ways in which English and American cultures converge and diverge within Moore's writings – particularly in relation to the arguments she rehearses in her essay ‘Henry James as a Characteristic American’ (1934) – this article shows how Moore's ‘English’ background cannot be regarded as incidental to her writing.